ARRANGEMENT AND DEVELOPMENT OF REPTIL PARK WITH ECOLOGICAL ARCHITECTURAL APPROACH IN PURBALINGGA - Kartika Sari, Dinda; Dwi Yudono, Yoh Wahyu; Lestariningsih, Dwi Jati (ReTII, 2021)
Purbalingga is considered the best district that packs tourism development, one of the most famous tourist destinations in Purbalingga Regency is the Reptile Park Tourism Object, namely Sanggaluri Park. The physical condition of Sanggaluri Park has a lot of damage that makes visitors feel uncomfortable, there is no renovation and there is still a lack of maintenance so that the facilities are getting worse day by day. From several existing facilities at Sanggaluri Park, it was found that there was a decrease in quality for humans and animals, animal show areas, cages, and also other facilities that needed to be improved to support the function as a place for conservation, recreation and education. The structuring and development efforts are intended to create a new direction or pattern without leaving the existing environmental context and one of them is the development of the Reptile Park area into a tourist attraction using environmental themes. It is hoped that using the Ecological Architecture approach can be an effort to care for the current and future environment, be able to protect and maintain nature and the ecosystem in it and can create comfort for its residents.